Graduate nurses' learning trajectories and experiences of Problem Based Learning: A focused ethnography study. - Spiers, J. A.; Williams, B.; Gibson, B.; Kabotoff, W.; McIlwraith, D.; Sculley, A.; Richard, E. (International Journal of Nursing Studies, 2014)
Background: Problem-based learning seeks to foster active, collaborative and self directed learning. It is increasingly utilized in health professional education; however, it is difficult to ascertain effectiveness. Empirically, student satisfaction does not match academic achievement but the reasons for this are unclear. Objective: To explore the experience trajectories and satisfaction of graduates who had completed an undergraduate problem-based learning nursing program. Design and methods: Qualitative focused ethnography using individual and group semi-structured interviews. Categories and themes were identified using inductive constant comparison. A comparative matrix analysis of differing levels of the two core processes illuminated specific experience profiles. Participants and setting: Forty five program graduates who had graduated between one and nine years previously from a Western Canadian program offered at four academic sites. The sample was mostly female (n = 37), aged 26-30 years (n = 23) and graduated 5-8 years previously (n = 20). Results: Levels of satisfaction with the program varied markedly. Two core processes contributed to this: ''understanding'' and ''valuing'' problem-based learning. Specific experience profiles included: ''Happy as fish in water'' which represents those who understood and valued the approach, and flourished; ''I'll do it but I won't like it'' reflects those who understood and could adjust to the academic context but did not particularly value it; ''I just want to be a nurse'' characterized those who consistently disliked and resisted the process but endured in order to graduate. Each profile was characterized by attitudes, intentions, learning preferences and program satisfaction. Conclusions: We theorize an underlying mechanism explaining these diverse levels of satisfaction are differing orientations to studying. This approach to understanding how students typically approach learning is strongly linked to perceptions of academic quality and program satisfaction in higher education research, although it has been neglected in nursing problem-based learning research. Orientations to studying include reproductive surface learning, deep learning for understanding and meaning, and strategic approaches to maximize desired objectives. These orientations are congruent with the descriptive typologies developed in this research. This provides an effective explanation as to why some students adapt easily and flourish in problem-based learning contexts, while others continually struggle to adapt. Further research is needed to determine the relationship between deep, surface, and strategic orientations to study and student satisfaction in nursing programs.